Interkingdom Comparison of Threonine Metabolism for Stem Cell Maintenance in Plants and Animals - Sahoo, Debee Prasad; Van Winkle, Lon J.; Díaz de la Garza, Rocío I.; Dubrovsky, Joseph G. (Frontiers in Cell and Developmental Biology, 2021)
In multicellular organisms, tissue generation, maintenance, and homeostasis depend on stem cells. Cellular metabolic status is an essential component of different differentiated states, from stem to fully differentiated cells. Threonine (Thr) metabolism has emerged as a critical factor required to maintain pluripotent/multipotent stem cells in both plants and animals. Thus, both kingdoms conserved or converged upon this fundamental feature of stem cell function. Here we examine similarities and differences in Thr metabolism-dependent mechanisms supporting stem cell maintenance in these two kingdoms. We then consider common features of Thr metabolism in stem cell maintenance and predict and speculate that some knowledge about Thr metabolism and its role in stem cell function in one kingdom may apply to the other. Finally, we outline future research directions to explore these hypotheses.